Co-digestion of primary sewage sludge with drinking water treatment sludge: A comprehensive evaluation of benefits. (June 2021) - Xie, Sihuang; Li, Xuan; Pham, Chau Uyen; Nguyen, Hoang Viet; Song, Yarong; Chetty, Kirthi; Kulandaivelu, Jagadeeshkumar; Wang, Chengduan; Hai, Faisal; Jiang, Guangming
Highlights: Critical dosages thresholds for AcoD of two types of DWTS and PS were identified. Limited methanogenesis inhibition was observed at lower ratios of DWTS. Positive downstream impacts (P & H2 S removals) were achieved with DWTS. Fe & Al-DWTS additions enriched vivianite and aluminium phosphate, respectively. Dominant methanogenic pathways were restructured differently by two DWTS. Abstract: Anaerobic co-digestion of primary sludge with two types of drinking water treatment sludge (DWTS), namely iron- or aluminum-rich DWTS (Fe- or Al-DWTS) were systematically evaluated by biochemical methane potential tests, kinetic modelling, downstream process parameters and microbial community analysis. Specific methane yields decreased approximately 19% to 123 mL·g −1 VS, while the hydrolysis constant k h decreased from 0.21 d −1 to 0.18 d −1 for Fe-DWTS at 10% to 40% dosages. On the contrary, specific methane yields decreased 45–55% for Al-DWTS, and k h decreased to 0.14 d −1 at 40% dosage. Significant removals (>95%) of phosphate and hydrogen sulfide were observed for Fe- and Al-DWTS additions at 40% dosage. Microbial community analysis revealed that Al-DWTS increased the abundance of most hydrogenotrophic methanogens, while Fe-DWTS increased the abundance of acetoclastic methanogens. Kinetic modelling further revealed that Fe- and Al-DWTS additions affected the hydrolysis and methanogenesis process kinetics and the methane yield differently.